IMPLEMENTASI PROGRAM AKSELERASI PENDIDIKAN - Warham Warham; Sumadi Sumadi; Alben Ambarita (9 772338317006)
This research intended to describe the implementation of accelerated program in education at State Senior High School 1 Terbanggi Besar Central of Lampung. There were eight things examined in this study, namely planing, organizing, implementation, controling, evaluating, supporting factors, inhibiting factors, and the customers satisfied of accelerated program in education at State Senior High School 1 Terbanggi Besar Central of Lampung. Research with qualitative approach. Data were collected using interviews, observation nonparticipant and documentation. Data were analyzed using the patterns of interaction Miles and Huberman have been modified. The findings showed: the planing, organizing, and implementation is done by the team of curiculum develovment. The support factors of accelerated program in education at State Senior High School I Terbanggi Besar Central of Lampung, namely: sum of teachers and a good qualification teachers, sum of superior intelligent students, a good infrastructur, and a good commitment. The inhibiting factors, namely make a schedule, suport government, teaching learning.Penelitian ini bertujuan untuk mengetahui implementasi program akselerasi di SMA Negeri 1 Terbanggi Besar Lampung Tengah, yang meliputi 8 sub fokus: perencanaan, pengorganisasian, pelaksanaan, pengawasan, evaluasi, faktor pendukung, faktor kendala dan kepuasan pelanggan program akselerasi pendidikan di SMA N 1 Terbanggi Besar. Penelitian ini menggunakan pendekatan kualitatif. Teknik pengumpulan data menggunakan wawancara, observasi nonpartisipan dan dokumentasi. Teknik analisis data menggunakan pola interaksi Miles dan Huberman yang telah dimodifikasi. Hasil penelitian menunjukkan bahwa perencanaan, pengorganisasian dan pelaksanaan program akselerasi dilakukan oleh tim pengembang kurikulum sekolah. Faktor pendukung program akselerasi pendidikan di SMA N 1 Terbanggi Besar ialah tersedianya dana yang memadai, kualifikasi dan kompetensi tendik, jumlah siswa cerdas istimewa yang memadai, tersedianya sarana prasarana yang dibutuhkan. Faktor kendalanya alah pengelolaan KBM belum optimal, dan kurangnya pembinaan pemerintah melalui Dinas Pendidikan Kabupaten maupun Provinsi.Keywords: program akselerasi di bidang pendidikan, pelaksanaan